Which scoring system is effective in predicting mortality in patients with Crimean Congo hemorrhagic fever? A validation study. (3rd April 2022) - Bakir, Mehmet; Öksüz, Caner; Karakeçili, Faruk; Baykam, Nurcan; Barut, Şener; Büyüktuna, Seyit Ali; Özkurt, Zülal; Öz, Murteza; Barkay, Orçun; Akdoğan, Özlem; Elaldi, Nazif; Hasbek, Murşit; et al.
ABSTRACT: We aimed to decide which scoring system is the best for the evaluation of the course of Crimean-Congo Hemorrhagic Fever (CCHF) by comparing scoring systems such as qSOFA (quick Sequential Organ Failure Assessment), SOFA (Sequential Organ Failure Assessment), APACHE II (Acute Physiology and Chronic Health Evaluation II) and SGS (Severity Grading System) in centers where patients with CCHF were monitored. The study was conducted with patients diagnosed with CCHF in five different centers where the disease was encountered most commonly. Patients having proven PCR and/or IgM positivity for CCHF were included in the study. The scores of the scoring systems on admission, at the 72 nd hour and at the 120 th hour were calculated and evaluated. The data of 388 patients were obtained from five centers and evaluated. SGS, SOFA and APACHE II were the best scoring systems in predicting mortality on admission. All scoring systems were significant in predicting mortality at the 72 nd and 120 th hours. On admission, there was a correlation between the qSOFA, SOFA and APACHE II scores and the SGS scores in the group of survivors. All scoring systems had a positive correlation in the same direction. The correlation coefficients were strong for qSOFA and SOFA, but poor for APACHE II. A one-unit rise in SGS increased the probability of death by 12.818 times. qSOFA did not provide significant results in predicting mortality on admission. SGS, SOFA and APACHE II performed best at admission and at the 72 nd and 120 th hours.